2001
DOI: 10.3354/ame024129
|View full text |Cite
|
Sign up to set email alerts
|

mmobilization and bacterial utilization of dissolved organic carbon entering the riparian zone of the alpine Enns River, Austria

Abstract: In order to understand the factors controlling the removal of riverine dissolved organic carbon (DOC) in the riparian zone of an alpine river, concentrations of DOC and dissolved oxygen, as well as bacterial abundance and production, were determined in interstitial waters of an experimental bank filtration site of the Enns River, Austria. Four porewater stations exhibiting differing sedimentologic and hydrologic characteristics were sampled over an annual cycle. We found that concentrations of DOC, oxygen, bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…These sites were chosen from a comprehensive survey of streams in western Montana (15) to encompass a range of sediment metal concentrations and other physical characteristics such as average discharge, substratum type, and drainage area ( Table 1 Sampling design. It has previously been indicated that particle size can affect community structure by altering flow rates, nutrient availability and recharge, and surface area available for colonization (11,43). Bed materials in freestone rivers in the Rocky Mountain West, including those in this study, are very heterogeneous in nature and distributed patchily, ranging from silt to cobbles.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…These sites were chosen from a comprehensive survey of streams in western Montana (15) to encompass a range of sediment metal concentrations and other physical characteristics such as average discharge, substratum type, and drainage area ( Table 1 Sampling design. It has previously been indicated that particle size can affect community structure by altering flow rates, nutrient availability and recharge, and surface area available for colonization (11,43). Bed materials in freestone rivers in the Rocky Mountain West, including those in this study, are very heterogeneous in nature and distributed patchily, ranging from silt to cobbles.…”
Section: Methodsmentioning
confidence: 94%
“…It is acknowledged that predation (33,38) and dissolved-organic-carbon quality and quantity (11,25,56,79) can have effects on the size and structure of microbial communities. Determining the effects of the former was beyond the scope of this investigation, and dissolved-organic-carbon levels VOL.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies in other streams have identified exogenous organic carbon as an important growth substrate for bacteria in the hyporheic zone (10,29,59). The majority of exogenous organic carbon that enters lotic ecosystems in this montane region arrives during the fall and early winter, primarily through deposition of leaf litter (18,59).…”
Section: Discussionmentioning
confidence: 99%
“…This coarse organic matter is processed by aquatic insects, fungi, and bacteria and is eventually entrained in the hyporheic zone as dissolved organic carbon (48,67). Entrainment of dissolved organic carbon normally promotes increased respiration and growth in hyporheic microbial communities (10,29,59). Thus, elevated heavy-metal levels in the hyporheic zone appear to inhibit the growth of group I and II organisms during the fall and early winter, when conditions may otherwise favor their growth.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between DOC concentration and the community structure of the epilithic, but not the sediment, community suggests that sources of organic carbon supporting secondary productivity partition differently between these two streambed habitats (42,54,56). While the epilithic populations are generally limited to dissolved carbon in the bulk flow and endogenous carbon (DOC and POC derived from the biofilm), the sediment populations likely obtain additional resources from entrained POC and DOC upwelling from the hyporheic zone (5,10,30,54). The appearance of both prokaryotic and eukaryotic primary producers in the epilithon during the summer months suggests a seasonal shift towards autocthonous carbon sources within this biofilm, as is also supported by prior estimates of autochthonous primary productivity in White Clay Creek (31).…”
Section: Discussionmentioning
confidence: 99%